Structural change and energy use in Ghana's manufacturing and agriculture sectors. (November 2022) - Amoako, Samuel; Andoh, Francis Kwaw; Asmah, Emmanuel Ekow
Abstract: This paper examines energy use under policy regime changes (that is, before and after the Economic Recovery Programme/Structural Adjustment Programme (ERP)/(SAP)) in Ghana, paying attention to the extent to which the regime switch moderates energy use in the agriculture and manufacturing sectors which are two key sectors of the economy. Employing the Ordinary Least Squares (OLS) and the Fully Modified Ordinary Least Squares (FMOLS) on data spanning 1971–2014, the study finds the structural change policy to be positively correlated with energy use. Agriculture and manufacturing also have positive impacts on energy use. As a policy direction, subsequent structural change policies that focus on increasing output, especially in the private sector, must come along with the needed energy use strategy. Also, the agriculture and manufacturing sectors should be focused on production mixes and systems that are energy efficient. Highlights: The study examines ERP/SAP on energy use in Ghana's manufacturing and agricultural sectors. Study uses Ordinary Least Squares (OLS) and the Fully Modified Ordinary Least Squares (FMOLS) on data spanning 1971–2014 Generally, energy use in the economy increased following the adoption of the ERP/SAP. However, intentional policy targeted manufacturing and agriculture sectors can reduce energy use in those sectors. Energy efficiency management systems are required to moderate industrial and agricultural energy use. A structural transformation programme should come with a clear efficient energy utilisation framework/strategy.